SISTEM PENGELOLAAN SAMPAH DI KABUPATEN MAGETAN - Azis Suhermanto (JI@P, 2018)
Relating to planning of waste management executed by LivingEnvirontment Agency of Magetan Regency this agency adopted newparadigm, that is to reduce and to utilize the waste as maximum aspossible by using 3R program. This method is intended to reduce theamount of disposed waste to the end of landfill (TPA). It indicated thatservice area with eight kelurahan the existing structure and infrastrucurewere considered quite to manage the existing amount of waste. Theoffice which has obligation and authority to manage the waste is the ofLiving Environtment Agency. This was based on Act no. 18 year of 2018.Its 60% of budget comes from the revenue of reggional budget (APBD)and the rest i.e. 25% comes from the reveneu of national budget(APBN), and 15% comes from the community retribution. In thecommunity level, the agency maximized service and developed what iscalled ‘bank of waste’ and to socialize the 3R program. Dealing with thecontrolling activities, it was done by the Living Environtment AgencyMagetan Regency.Key words: planning; organizing; directing; controlling.